2022
DOI: 10.1021/acs.jmedchem.1c01265
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the RAS:PDE6D Complex Is a Novel Strategy to Inhibit RAS Signaling

Abstract: RAS is a major anticancer drug target which requires membrane localization to activate downstream signal transduction. The direct inhibition of RAS has proven to be challenging. Here, we present a novel strategy for targeting RAS by stabilizing its interaction with the prenyl-binding protein PDE6D and disrupting its localization. Using rationally designed RAS point mutations, we were able to stabilize the RAS:PDE6D complex by increasing the affinity of RAS for PDE6D, which resulted in the redirection of RAS to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Moreover, the combination of C14 and P8 caused a 99% reduction in the clonogenicity of PDAC cells. The structural basis for KRas4B/PDE6δ complex formation and simultaneous binding of molecules has been recently demonstrated ( Yelland et al, 2022 ). This study confirmed our previous finding that sequestering this complex in the cytosol prevents KRas activation at the plasma membrane and downstream ERK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combination of C14 and P8 caused a 99% reduction in the clonogenicity of PDAC cells. The structural basis for KRas4B/PDE6δ complex formation and simultaneous binding of molecules has been recently demonstrated ( Yelland et al, 2022 ). This study confirmed our previous finding that sequestering this complex in the cytosol prevents KRas activation at the plasma membrane and downstream ERK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Another complication of PDE6D as a drug target is its intrinsically broad cargo spectrum. , Therefore, its inhibition will affect not only K-Ras and thus KRAS mutant cancer cells but also a host of PDE6D cargos. Finally, the ontogenetic role of PDE6D may be worth considering.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Ras membrane targeting remains a promising strategy for inhibitor development. , The trafficking chaperone PDE6D (or PDEδ) has been proposed as a surrogate drug target in KRAS mutant cancers . PDE6D possesses a hydrophobic pocket, which can bind to one or even two prenyl moieties, thus having a cargo spectrum that comprises farnesylated or geranylgeranylated Ras and Rho family proteins as well as Rab proteins. , Only proteins that are not in addition palmitoylated in the vicinity of the prenylated cysteine are accepted as cargo, making mono- and dual-palmitoylated N-Ras, K-Ras4A, and H-Ras effectively worse PDE6D cargo in cells than K-Ras4B (hereafter K-Ras) . Cargo affinity is critically modulated by the four residues upstream of the prenylated cysteine.…”
Section: Introductionmentioning
confidence: 99%
“…Similar responses were reported for Deltarasin, an effect attributed to active function and efflux by ABC transporter proteins although we cannot exclude other mechanisms in Tsc2-null MEF cells ( Zimmermann et al, 2013 ). At least for cancer cell lines, it is known that PDEδ is highly expressed up to single digit micromolar ranges ( Yelland et al, 2022 ). Hence, equally high concentrations of PDEδ inhibitors are needed to interfere with the interaction of PDEδ and its client proteins.…”
Section: Discussionmentioning
confidence: 99%